Delayed Administration of Tat-HA-NR2B9c Promotes Recovery After Stroke in Rats. Issue 5 (May 2015) - Zhou, Hai-Hui; Tang, Ying; Zhang, Xin-Yong; Luo, Chun-Xia; Gao, Li-Yan; Wu, Hai-Yin; Chang, Lei; Zhu, Dong-Ya
<x xml:space="preserve">Abstract</x> Background and Purpose— Previous studies reported that Tat-NR2B9c, a peptide disrupting the N-methyl-D-aspartate receptor–postsynaptic density protein-95 interaction, reduced ischemic damage in the acute phase after stroke. However, its effect in the subacute phase is unknown. The aim of this study is to determine whether disrupting the N-methyl-D-aspartate receptor–postsynaptic density protein-95 interaction in the subacute phase promotes recovery after stroke. Methods— Studies were performed on Sprague-Dawley rats or nNOS−/− mice, and experimental ischemic stroke was induced by middle cerebral artery occlusion. Animals were treated with drugs starting at day 4 after ischemia. Sensorimotor functions and spatial learning and memory ability were assessed after drug treatment. Then, rats were euthanized for morphological observation and biochemical tests. Results— Disrupting the N-methyl-D-aspartate receptor–postsynaptic density protein-95 interaction with Tat-HA-NR2B9c significantly ameliorated the ischemia-induced impairments of spatial memory and sensorimotor functions in rats during subacute stage but did not improve stroke outcome in nNOS−/− mice. Consistent with the functional recovery, Tat-HA-NR2B9c substantially increased neurogenesis in the dentate gyrus and dendritic spine density of mature neurons in the motor cortex of rats, meanwhile, reversed the ischemia-induced formation of S-nitrosylation-cyclin-dependent kinase 5 and increased cyclin-dependent kinase 5 activity in ipsilateral hippocampus. However, directly blocking N-methyl-D-aspartate receptors with MK-801 or Ro 25-6981 did not show the beneficial effects above. Conclusions— Dissociating N-methyl-D-aspartate receptor–postsynaptic density protein-95 coupling by Tat-HA-NR2B9c in the subacute phase after stroke promotes functional recovery, probably because of that it increases neurogenesis and dendritic spine density of mature neurons via regulating cyclin-dependent kinase 5 in the ischemic brain.